Customers’ Perception on Islamic Crowdfunding as A Possible Financial Solution For The Pandemic Covid 19 Crisis in Malaysia - Dzuljastri Abdul Razak; Syamsu Rizal Zulmi; Qosdan Dawami (Journal of Islamic Finance, 2021)
The COVID 19 pandemic has brought an unprecedented crisis globally and people are still struggling for solutions to deal with the crisis. The effect is very broad-based be it on a social, economic, and healthy way of living. The purpose of this study is to investigate customers’ perception of Islamic Crowd Funding (ICF) as a possible financial solution for the pandemic crisis. Several factors such as the concept of ICF, justice and fairness and acceptance of ICF were used. A total of 322 responses were collected through questionnaires to investigate the validity of the proposed model. SPSS was used to analyse the data collected using reliability, correlation and multiple regression. The result indicated that the concept of ICF, justice and fairness significantly influenced the acceptance of Islamic crowdfunding. Hence, practitioners should emphasize these values to attract customers during this COVID 19 crisis. The result of this study further contributed to the new body of knowledge on ICF as a solution to the pandemic COVID 19 crisis.